Empirical Analysis of Sustainable Performance in Relation to Stock Exchange Performance: Evidence from Romania - Vilena Tiscenco; Veronica Grosu; Galina Bădicu; Cristina Gabriela Cosmulese (Studies and Scientific Researches: Economics Edition)
Given the substantial advancements in worldwide financial markets and the sharp increase in sustainability concerns, this article proposes an incursion into the empirical analysis of the interaction between companies' sustainable performance and stock market performance, focusing on the specificities of the Romanian financial market. It emphasizes the importance of a comprehensive approach that goes beyond simple financial figure analysis to include aspects such as sustainability, corporate governance, and social impact. The article aims to shed light on this complex relationship through rigorous empirical analysis applied to data specific to the Romanian market. We will thoroughly investigate the connections between companies' sustainability practices and the evolution of stock prices, taking into account the economic particularities of Romania, culminating with the estimation of a multiple linear regression model. Our study reveals that there is a correlation between the market capitalization of a company, its corporate performance and the specific industry or sector in which it operates.